Systematic mapping study on verification and validation of industrial third-party IoT applications - Tritchkov Ivan (Lviv Politechnic Publishing House, 2020)
The next industrial revolution commonly known as Industry 4.0 represents the idea of interconnected manu facturing, where intelligent devices, systems and processes exchange information, resources and artifacts to optimize the complete value-added chain and to reduce costs and time-tomarket. Industrial software ecosystems are a good example how the latest digitalization trends are applied in the industry domain and how with the help of industrial IoT applications the production process can be optimized. However, the use of third-party applications exposes to a risk the systems and devices part of the manufacturing process. To address these risks a set of quality measures must be carried out in the ecosystem. This paper presents the results of a systematic mapping study carried out in the area of verification and validation of industrial IoT third-party applications. The goal of the study is to structure the scientific landscape and to provide an up-to-date snapshot of the current state of the research field.
Keywords: industrial applications, industrial ecosys tems mapping, IoT, mapping study, quality assurance, testing, verification, validation , third party